KEANEKARAGAMAN JENIS TUMBUHAN BAWAH TANAMAN AKASIA (Acacia mangium Willd) DI BUKIT PENGHIJAUAN MANDOR KABUPATEN LANDAK - Goreti, Teodora; Muin, Abdurrani; Burhanuddin, Burhanuddin (JURNAL HUTAN LESTARI, 2021)
Acacia mangium plantations in Bukit Penghijauan has grown by various species of understoreys. This study aims are to examine uderstoreys diversity and determine the amount of species and dominant of understoreys that’s growing under Acacia stands in Bukit Penghijauan Mandor Landak District. The study used a survey method with a systematic sampling of squares. Laying of plots was carried out by purposive sampling in area where are acacia plants. The size of plot is 10 m x 10 m, devided in to 25 sample plots of size 2 m x 2 m. Prymary data on taken involve species name, amount of individuals each species and herbarium specimens as identification device. The study result swowed that understoreys that be discovered under acacia stands in Bukit Penghijauan Mandor Landak District as much 21 species. The domination that species is paku resam (Gleichenia linearis Burm Clarke), rumput bede (Paspalum conjugatum Berg) and akar rambat (Psychotria sarmentosoides).Keywords : Bukit penghijauan, Species diversity, Understoreys.